Experimental study of mechanical properties of Sisal/banana fiber hybrid sandwich composite. (2022) - Chithra Devi, R.; Girimurugan, R.; Nanthakumar, S.; Rajasekaran, P.; Hasane Ahammad, S.K.; Joe Patrick Gnanaraj, S.
Abstract: Composites are becoming increasingly popular as a result of their useful features, like higher strength-to-weight ratio, higher modulus-to-weight ratio, resistance to corrosion and abrasive resistance. The purpose of this study is to examine the impact of moisture absorption on the mechanical characteristics of hybridized sandwich composite scaffolds made from epoxy resin, strengthened by woven fabrics of banana (B) and Sisal (S) fibers, and a fundamental layer of polyethylene foam (F). The buildings in this investigation were made using a hand layup approach. Samples of the composite are submerged in room-temperature water for varying amounts of time to determine the fibers' water absorption qualities. Several sandwich composite constructions are made and compared to a composite made from 100% Sisal fiber. According to the results, including foam into the Sisal/banana fibres increases their mechanical qualities. However, the composites' tensile, flexural, and impact strengths were diminished after prolonged exposure to water due to water permeating the fibre/matrix contact.